2021
DOI: 10.1101/2021.03.02.433553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A CTDNEP1-lipin 1-mTOR regulatory network restricts ER membrane biogenesis to enable chromosome motions necessary for mitotic fidelity

Abstract: The endoplasmic reticulum (ER) dramatically restructures in open mitosis to become excluded from the mitotic spindle; however, the significance of ER reorganization to mitotic progression is not known. Here, we demonstrate that limiting ER membrane biogenesis enables mitotic chromosome movements necessary for chromosome biorientation and prevention of micronuclei formation. Aberrantly expanded ER membranes increase the effective viscosity of the mitotic cytoplasm to physically restrict chromosome dynamics - sl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 65 publications
(91 reference statements)
0
13
0
1
Order By: Relevance
“…Our 3D EM images of ensheathed chromosomes show that microtubules face a difficult task to negotiate several layers of endomembranes in order to make the contact between kinetochore and spindle that is necessary for rescue and alignment. In cases where contact is made, endomembranes are also likely to impair the congression of the chromosome, as suggested by a recent study where excess ER was shown to slow chromosome motions (Merta et al, 2021). Since endomembranes are a risk factor for missegregation, their precise organization – for example the sheet-to-tubule ratio of the ER – may influence the likelihood for missegregation (Champion et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our 3D EM images of ensheathed chromosomes show that microtubules face a difficult task to negotiate several layers of endomembranes in order to make the contact between kinetochore and spindle that is necessary for rescue and alignment. In cases where contact is made, endomembranes are also likely to impair the congression of the chromosome, as suggested by a recent study where excess ER was shown to slow chromosome motions (Merta et al, 2021). Since endomembranes are a risk factor for missegregation, their precise organization – for example the sheet-to-tubule ratio of the ER – may influence the likelihood for missegregation (Champion et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Our conclusion is that the endomembranes do not necessarily prevent contact with ensheathed chromosomes but they appear to make contact less likely or less productive. Even in cases where contact is made, endomembranes are likely to impair the congression of the chromosome, as suggested by a recent study where excess ER was shown to slow chromosome motions (Merta et al, 2021). Since endomembranes are a risk factor for missegregation, their precise organization -for example the sheet-to-tubule ratio of the ER -may influence the likelihood for missegregation (Champion et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like in yeast, removal of lipins in protozoa, plants, worms, and flies causes ER expansion (Golden et al , 2009; Eastmond et al , 2010; Bahmanyar et al , 2014; Grillet et al , 2016; Pillai et al , 2017). Similarly, removal of the Nem1 ortholog CTDNEP1 causes ER expansion in human tissue culture cells (preprint: Merta et al , 2021). However, while both yeast and metazoa use the CDP‐DAG pathway to synthesize phosphatidylinositol, metazoa mainly generate phosphatidylcholine and phosphatidylethanolamine through the Kennedy pathway (Vance, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we focused on the protein phosphatase CTD-nuclear envelope phosphatase 1 (CTDNEP1, formerly known as Dullard; Nem1 in S. cerevisiae, CNEP-1 in C. elegans) because of its conserved role in controlling the production of ER and nuclear membranes (Siniossoglou et al, 1998;Santos-Rosa et al, 2005;O'Hara et al, 2006;Kim et al, 2007;Han et al, 2012;Bahmanyar et al, 2014;Jacquemyn et al, 2021;Merta et al, 2021). CTDNEP1 is enriched at the nuclear envelope and maintains a stable, dephosphorylated pool of the phosphatidic acid phosphatase lipin 1, the main enzyme that produces diacylglycerol (DAG) in the ER (Siniossoglou et al, 1998;Han et al, 2012;Merta et al, 2021;Lee et al, 2023). CTDNEP1 opposes stimulatory signals from nutrient sensing pathways that retain phosphorylated lipin 1 in the cytoplasm (Merta et al, 2021).…”
Section: Introductionmentioning
confidence: 99%